Assessing motivators and barriers to active healthy living among a multicultural college student body: A qualitative inquiry. Issue 2 (12th February 2023) - Leinberger-Jabari, Andrea; Al-Ajlouni, Yazan; Ieriti, Maddalena; Cannie, Scott; Mladenovic, Marko; Ali, Raghib
Abstract: Lack of physical activity and poor eating habits have been associated with numerous negative health outcomes, including diabetes, cardiovascular disease, and obesity. Previous research demonstrated that physical activity decreases throughout young adulthood and adolescence. This was a qualitative investigation into potential barriers and motivators to healthy eating and being physically active among a diverse group of college students in a US institution in the Middle East. A total of six focus groups were conducted (N = 35) to discuss motivators and barriers to healthy eating and being physically active, perceptions, culture, and intervention ideas. Stress and time management emerged as barriers, while social supports were a motivating factor for students. Future research should investigate the unique effect of transitioning into college in the context of the Middle East. Interventions targeting factors that affect the physical activity and eating habits of young adults can help improve longer-term health outcomes.